Rekonstruksi Perkawinan Nyentana dalam Masyarakat Bali: Perspektif Kesetaraan Gender - Dharmayani, Dharmayani; Karini, Eti; Ismail , Habib; Iwaannudin, Iwaannudin; Arsyad, Mufid (Tasyri' : Journal of Islamic Law, 2025)
This research aims to explore and analyze the reconstruction of nyentana marriage in Balinese society from a gender equality perspective. Nyentana marriage, which involves the groom living with the bride's family, is a unique tradition that has the potential to elevate the status of women and promote gender equality. However, negative stigma towards this type of marriage still exists in certain segments of Balinese society, as it is considered to conflict with the dominant patrilineal customary norms. This study uses a qualitative approach with a case study method in several regions of Bali, including Tabanan, Gianyar, and Badung. Data were collected through in-depth interviews with couples practicing nyentana marriage, customary leaders, and religious figures, as well as participatory observations during nyentana wedding ceremonies. Thematic analysis was employed to identify the factors influencing the acceptance or rejection of this tradition and its impact on gender equality. The research findings indicate that despite challenges posed by negative stigma, nyentana marriage has the potential to alter social structures and strengthen the position of women in Balinese society. Therefore, the role of customary institutions and religious leaders is crucial in supporting a better understanding of gender equality through this tradition. This research is expected to provide new insights into how the nyentana marriage tradition can contribute to achieving gender equality goals and support sustainable development in Bali.